Comparing the values of intact parathormone and 1- 84 PTH to predict hyperparathyroidism in hemodialysis patients - Aria Jenabi; Mosadegh Jabbari; Hossein Ziaie (Society of Diabetic Nephropathy Prevention, 2017)
Background: Secondary hyperparathyroidism (SHPT) is a common complication of chronic kidney disease (CKD) leading high mortality and even long-term morbidity. SHPT is manifested by elevation of parathyroid hormone (PTH) and accurate determining the level of serum PTH is very essential for early diagnosis of SHPT secondary to CKD. It is very important to match the values obtained for intact parathormone (iPTH) and 1- 84 PTH with the minimized measurement bias. Objectives: The present study aimed to first determine the agreement value between the iPTH and 1- 84 PTH measures in patients with hyperparathyroidism secondary to endstage renal disease under chronic hemodialysis. Then, we attempted to determine the best cutoff values for these two measurements for detecting SHPT in such patients. Patients and Methods: This cross-sectional study was conducted on hemodialysis patients. The value of study biomarkers including iPTH and 1- 84 PTH was assessed. Results: A strong positive association was revealed between the two indicators of iPTH and 1-84 PTH (r = 0.800, P < 0.001). The linear association between these two parameters is independent to baseline characteristics including gender, age, body mass index, and medical history. Among all biochemical elements, the value of 1-84 PTH was only associated with serum calcium level negatively (r = -0.267, P = 0.027) and alkaline phosphatase positively (r = 0.359, P = 0.003). Considering iPTH as the reference and according to the area under the ROC curve (AUC), 1-84 PTH had high value to predict hyperparathyroidism (AUC = 0.926, P < 0.001). The best cutoff point for 1-84 PTH to discriminate hyperparathyroidism from normal condition was 60 yielding a sensitivity of 92.3% and a specificity of 79.1%. Among other baseline laboratory parameters, only alkaline phosphatase had an acceptable value for diagnosing hyperparathyroidism (AUC = 0.731, P = 0.001). Conclusions: The measurement of both iPTH and 1-84 PTH is valuable for predicting hyperparathyroidism secondary to CKD, but according to lower cost and comparableeffectiveness of iPTH measurement, this assay may be comparable to 1-84 PTH to predict this consequence.